If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(4r + -7) + -4(r + -3) = 0 Reorder the terms: 3(-7 + 4r) + -4(r + -3) = 0 (-7 * 3 + 4r * 3) + -4(r + -3) = 0 (-21 + 12r) + -4(r + -3) = 0 Reorder the terms: -21 + 12r + -4(-3 + r) = 0 -21 + 12r + (-3 * -4 + r * -4) = 0 -21 + 12r + (12 + -4r) = 0 Reorder the terms: -21 + 12 + 12r + -4r = 0 Combine like terms: -21 + 12 = -9 -9 + 12r + -4r = 0 Combine like terms: 12r + -4r = 8r -9 + 8r = 0 Solving -9 + 8r = 0 Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '9' to each side of the equation. -9 + 9 + 8r = 0 + 9 Combine like terms: -9 + 9 = 0 0 + 8r = 0 + 9 8r = 0 + 9 Combine like terms: 0 + 9 = 9 8r = 9 Divide each side by '8'. r = 1.125 Simplifying r = 1.125
| 4-2(x-5)=1 | | 7c+3=4c+21 | | 16/128=24/x | | 13x+4y=7 | | 5p+4=19 | | 2(p+3)=3 | | 3(t-3)+5t=4(2t+4)-12 | | (10x-3)=(8x+1) | | 7x+4forx=6 | | 10x(4+2)= | | 9y^2+8y-12=6y | | Logx(8-2x)=2 | | 3p-13=11+9p | | 5z=9z-8 | | 3p-13=11+9 | | (5x-8)2=(5x+12)2 | | -6(x-2)=x+5 | | t*4-2=16 | | 4x^4+2x^2-20x=0 | | X+5*3x-2= | | (3-5x)/(2x-4)=0 | | 2x+3x=15findx | | 18x^2/10y^2*15y^3/24x | | 23-2=x-2+7 | | -2+2w=-4 | | 5(x+5)=7(2x-6) | | x/5-5=15 | | -x+x+5=0 | | (X+5)=7(2x-6) | | 6(3s+6)=54 | | 11m+1=8m+4 | | 6y-2=4y+14 |